Genetically Predicted Frailty Index Is Associated With Increased Risk of Multiple Metabolic Diseases: 175 226 European Participants in a Mendelian Randomization Study - Hexing Wang; Haifeng Zhang; Dongliang Tang; Yinshuang Yao; Junlan Qiu; Xiaochen Shu (Journal of Diabetes)
ABSTRACT Background A relationship between frailty index (FI) and metabolic diseases (MDs) has been reported in previous observational studies. However, the causality between them remains unclear. This study aimed to examine the causal effect of FI on MDs. Methods We performed a bidirectional two‐sample Mendelian randomization (MR) study. A recent large‐scale genome‐wide association study (GWAS) provided available data associated with FI, and summary statistics on eight MDs were collected from the IEU OpenGWAS database. Inverse variance weighted (IVW) was used as the main analysis to estimate causal effects, together with MR pleiotropy residual sum and outlier (MR‐PRESSO), MR‐Egger, Cochran's Q test, pleiotropy test, leave‐one‐out method, and MR Steiger analysis were used in the sensitivity analyses. Results Our MR study demonstrated for the first time that elevated FI was causally associated with an increased risk of MDs including obesity (odds ratio [OR] = 1.78; 95% confidence interval [CI]: 1.17–2.70; p = 0.0075), T2DM (OR = 1.67; 95% CI: 1.24–2.24; p = 6.95 × 10−4), gout (OR = 2.45; 95% CI: 1.29–4.64; p = 0.006), hypothyroidism (OR = 1.96; 95% CI: 1.47–2.60; p = 3.47 × 10−6), and HTN (OR = 2.17; 95% CI: 1.72–2.74; p = 5.25 × 10−11). However, no causal association was found between FI and osteoporosis, vitamin D deficiency, and hyperthyroidism. Conclusions Our findings support a causal relationship between FI and multiple MDs. This is crucial for the prevention of associated MDs in patients with frailty.